Electrostatic oil-purifying hydrogel as well as preparation method and application thereof

By defining the raw material components and ratios of the electrostatic oil purification hydrogel, a hydrogel with excellent hydrophilic oleophobicity and mechanical stability is formed, which solves the shortcomings of the existing electrostatic oil purification material dehydration technology and significantly improves the dehydration effect of waste oil products.

CN119708384AActive Publication Date: 2025-03-28STATE GRID HEBEI ELECTRIC POWER RES INST +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411656630.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The dehydration technology of existing electrostatic oil purification materials has problems such as long time, large area, inability to operate continuously, new impurities and large energy consumption, and it is difficult to effectively improve the dehydration effect of waste oil products.

Method used

By defining the raw material components and ratios of the electrostatic oil-purified hydrogel, materials such as lignin sulfonate, chitosan and acrylic acid are used to combine initiators and crosslinking agents to form hydrogels with excellent hydrophilic oleophobicity and mechanical stability.

Benefits of technology

It significantly improves the dehydration effect of electrostatic oil purification materials, can reduce the microwater content in waste transformer oil from 32mg/L to below 23mg/L, has high water absorption capacity and mechanical stability, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708384A_ABST
    Figure CN119708384A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrostatic oil purification materials, and particularly discloses electrostatic oil purification hydrogel as well as a preparation method and application thereof. The electrostatic oil-purifying hydrogel is prepared from the following raw materials in parts by mass: 1 to 6 parts of lignosulfonate, 5 to 8 parts of chitosan, 50 to 85 parts of acrylic acid, 130 to 200 parts of strong alkali solution, 1 to 3 parts of initiator, 0.1 to 0.3 part of cross-linking agent and 100 to 150 parts of water. Lignosulfonate, chitosan and acrylic acid are used as main raw materials, under the action of an initiator and a cross-linking agent, all the raw materials are cross-linked into a polymer, and the electrostatic oil-purifying hydrogel is obtained. By limiting the raw material components and proportion, the synergistic interaction effect of all the raw materials is effectively exerted, so that the electrostatic oil-purifying hydrogel has excellent hydrophilic and oleophobic properties, high mechanical stability and recycling capability, can be applied to various extreme use conditions, is suitable for large-scale industrial production, and has high market application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrostatic oil-cleaning materials, and in particular to an electrostatic oil-cleaning hydrogel and a preparation method and application thereof. Background Art

[0002] As the main insulating medium of oil-filled electrical equipment, the performance of insulating oil will directly affect the safe operation of the equipment. At present, with the continuous increase in the capacity of substation equipment, the importance of safe and reliable operation of substation equipment is also increasing. During the operation of the transformer, transformer oil (main components include cycloalkanes, alkanes and aromatic hydrocarbons, etc.) is prone to aging under the influence of external physical and chemical factors, and will produce moisture, oxygen and various oxides, which will greatly reduce its physical, chemical and electrical properties, especially the insulation performance of transformer oil, and even be forced to be scrapped.

[0003] As one of the key parameters for measuring transformer oil performance, the water content has a significant impact on the performance of transformer oil. Therefore, removing the water content in the oil to reduce it to the national standard (GB / T7595-2017 "Operation Transformer Oil Quality Standard", 25mg / L) can effectively improve the performance of waste transformer oil and is one of the important steps in the waste oil regeneration process. Compared with the traditional oil-water separation process, wettability materials have the advantages of energy saving, simple operation, high separation efficiency and wide application range. Researchers use methods such as chemical grafting, physical blending, surface coating or in-situ growth to introduce hydrophilic groups into electrostatic oil purification materials to enhance the hydrophilicity of electrostatic oil purification materials, thereby improving the separation efficiency. However, the dehydration technology commonly used in industry currently has more or less some disadvantages, such as long dehydration time, large floor space, inability to operate continuously, introduction of new impurities and high energy consumption. Therefore, it is urgent to develop an electrostatic oil purification material with excellent mechanical stability, which can not only save energy and reduce consumption, but also significantly increase the dehydration effect of waste oil products. Summary of the invention

[0004] In view of the above problems, the present invention provides an electrostatic oil-cleaning hydrogel and a preparation method and application thereof. By limiting the raw material components and ratios of the electrostatic oil-cleaning hydrogel, the hydrophilicity and oleophobicity and mechanical stability of the electrostatic oil-cleaning material are improved, and its dehydration effect on waste oil products is significantly increased.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] In a first aspect, the present invention provides an electrostatic clean oil hydrogel, comprising the following raw materials in parts by weight: 1 to 6 parts of lignin sulfonate, 5 to 8 parts of chitosan, 50 to 85 parts of acrylic acid, 130 to 200 parts of strong alkaline solution, 1 to 3 parts of initiator, 0.1 to 0.3 parts of cross-linking agent and 100 to 150 parts of water.

[0007] Compared with the prior art, the electrostatic oil-cleaning hydrogel provided by the present invention uses lignin sulfonate, chitosan and acrylic acid as main raw materials, and under the action of an initiator and a cross-linking agent, the raw materials are cross-linked into a polymer to obtain an electrostatic oil-cleaning hydrogel. As cross-linked organic substances that react with acrylic acid, lignin sulfonate and chitosan both have extremely strong water absorption and are the main raw materials for dehydrating waste oil products; acrylic acid is the main monomer for forming the hydrogel, and a strong alkaline solution can react with acrylic acid to neutralize, providing conditions for the polymerization of organic substances.

[0008] The present invention effectively exerts the synergistic effect of each raw material by limiting the raw material components and proportions, so that the electrostatic oil-cleaning hydrogel has excellent hydrophilicity and oleophobicity. In addition, the electrostatic oil-cleaning hydrogel provided by the present invention also has strong mechanical stability and recycling ability, can be applied to a variety of extreme conditions of use, is suitable for large-scale industrial production, and has high market application value. The results of the embodiment show that the electrostatic oil-cleaning hydrogel is applied to the dehydration of industrial oil products, and the micro-water content in waste transformer oil can be reduced from 32 mg / L to below 23 mg / L. The maximum volume expansion rate of the electrostatic oil-cleaning hydrogel reaches 57.5 times, and it has excellent water absorption capacity. The dehydration effect is extremely significant, which provides a new direction and industrialization path for the field of oil dehydration.

[0009] Preferably, the lignin sulfonate comprises sodium lignin sulfonate.

[0010] Preferably, the strong alkaline solution comprises 20 wt % to 50 wt % of potassium hydroxide aqueous solution.

[0011] Preferably, the initiator comprises potassium persulfate.

[0012] Preferably, the cross-linking agent comprises N,N'-methylenebisacrylamide.

[0013] In the present invention, potassium persulfate, as an initiator of the cross-linking reaction, has a strong oxidizing effect and can generate free radicals after reacting with the monomer, thereby promoting the chain initiation process of the organic cross-linking reaction. N,N'-methylenebisacrylamide has a unique functional group and can connect acrylic acid molecular monomers with chitosan to form a gel polymer with a mesoporous structure.

[0014] Illustratively, the water is deionized water.

[0015] Preferably, the electrostatically clean oil hydrogel has a mesoporous structure.

[0016] Preferably, the specific surface area of ​​the electrostatic oil-free hydrogel is 36 m 2 / g~42m 2 / g, pore volume is 0.01m 3 / g~0.113m 3 / g.

[0017] Preferably, the electrostatically clean oil hydrogel is prepared from the raw materials by a sol-gel method.

[0018] In a second aspect, the present invention provides a method for preparing the electrostatic oil-free hydrogel, comprising the following steps:

[0019] S1, weighing various raw materials according to the designed ratio, adding acrylic acid into a strong alkaline solution to carry out a neutralization reaction to obtain an acrylate solution;

[0020] S2, adding lignin sulfonate, chitosan, an initiator and a cross-linking agent into water to obtain a mixed solution;

[0021] S3, mixing the acrylate solution and the mixed solution, and performing a cross-linking reaction at 70° C. to 90° C. to obtain an electrostatic clean oil hydrogel.

[0022] It should be noted that there is no limitation on the order between S1 and S2.

[0023] The preparation method of the electrostatic oil-cleaning hydrogel provided by the present invention synthesizes the hydrophilic and oleophobic electrostatic oil-cleaning hydrogel by a simple sol-gel method, has a simple process, does not require complicated equipment and excessive energy consumption, reduces the preparation cost, and is suitable for large-scale production. The present invention has found through a large number of experiments that if the cross-linking temperature is too high, the acrylic acid monomer will fail, and thus the hydrogel polymer cannot be formed; if the cross-linking temperature is too low, the reaction will not proceed sufficiently and thoroughly, the reaction speed will be slow, and the efficiency will be low.

[0024] Preferably, in S1, the neutralization reaction temperature is 5°C to 40°C, and the reaction time is 0.5min to 1.5min.

[0025] In the present invention, a sufficient amount of strong alkali solution can rapidly react with acrylic acid to generate acrylate and water, and the neutralization reaction can generally be completed within 1 minute.

[0026] For example, in S1, after the neutralization reaction is completed, the process further includes cooling to room temperature.

[0027] For example, in S2, lignin sulfonate can be first added into water, and after it is completely dissolved, chitosan, initiator and cross-linking agent are added and mixed evenly to obtain a mixed solution.

[0028] Preferably, in S3, the cross-linking reaction time is 2 h to 3 h.

[0029] For example, in S3, after the cross-linking reaction is completed, washing and drying are also included. The hydrogel (brown) after the cross-linking reaction can be washed with an alcohol solution until the washing solution is colorless, such as washing with anhydrous ethanol for 3 to 4 times, and then placed in a constant temperature vacuum drying oven at 60°C to 70°C and 700Pa to 800Pa, and vacuum dried for 3h to 4h.

[0030] In a third aspect, the present invention provides an application of the electrostatic oil-cleaning hydrogel in the dehydration of industrial oil products.

[0031] In a fourth aspect, the present invention provides a method for using the electrostatic oil-cleaning hydrogel, comprising the following steps:

[0032] The electrostatic oil-cleaning hydrogel is mixed with the circulating oil product to be purified for purification.

[0033] Preferably, the volume ratio of the electrostatic oil-cleaning hydrogel to the oil to be purified is (7.5-8.5) cm 3 :10L.

[0034] Preferably, the electrostatic oil purification hydrogel is placed at least one of the positive electrode plate, the negative electrode plate, between the positive and negative electrode plates or at the oil inlet of the electrostatic oil purification reactor.

[0035] In the present invention, the electrostatic oil purification hydrogel is placed in any of the above positions in the electrostatic oil purification reactor, which can reduce the water content of the waste transformer oil to below 25 mg / L, meeting the requirements of the national standard GB / T7595-2017 "Quality Standard for Operating Transformer Oil".

[0036] Further preferably, the electrostatic oil purification hydrogel is placed at least one of the positive electrode plate or the negative electrode plate of the electrostatic oil purification reactor.

[0037] The electrostatic oil-cleaning hydrogel is placed on the electrode plate of the electrostatic oil-cleaning reactor. When the electrostatic oil-cleaning hydrogel is added to the electrostatic oil-cleaning reactor, the roughness and non-uniformity of the electrode plate are increased, thereby increasing the electric field gradient in disguise and making the purification effect more excellent.

[0038] Preferably, the purification temperature is 35°C to 55°C.

[0039] Preferably, the purification adopts a DC voltage, and the DC voltage is 12kV to 16kV.

[0040] Preferably, the circulation flow rate of the oil product to be purified is 0.1 m / s to 0.3 m / s.

[0041] The present invention can control the circulation flow rate of the oil product to be purified by installing a flow regulating pump on the oil pipe.

[0042] Preferably, the purification time is 25 min to 40 min.

[0043] The present invention has found through a large number of experiments that the oil purification effect can be optimized by controlling the above purification conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The SEM images of the hydrogels of Examples 1 to 3 and Comparative Example 1 of the present invention; wherein a represents the SEM image of the hydrogel of Comparative Example 1, b represents the SEM image of the electrostatically cleaned oil hydrogel of Example 1, c represents the SEM image of the electrostatically cleaned oil hydrogel of Example 2, and d represents the SEM image of the electrostatically cleaned oil hydrogel of Example 3;

[0045] Figure 2 The mechanical properties test diagram of the hydrogels of Examples 1 to 3 of the present invention and Comparative Example 1;

[0046] Figure 3 This is a N2 adsorption-desorption curve of the electrostatic oil-cleaning hydrogel of Example 1 of the present invention;

[0047] Figure 4 This is a specific surface area and pore size analysis diagram of the electrostatic clean oil hydrogel of Example 1 of the present invention;

[0048] Figure 5 This is a N2 adsorption-desorption curve of the electrostatic oil-cleaning hydrogel of Example 2 of the present invention;

[0049] Figure 6 This is a specific surface area and pore size analysis diagram of the electrostatic clean oil hydrogel of Example 2 of the present invention;

[0050] Figure 7 This is a N2 adsorption-desorption curve diagram of the electrostatic oil-cleaning hydrogel of Example 3 of the present invention;

[0051] Figure 8 This is a specific surface area and pore size analysis diagram of the electrostatic clean oil hydrogel of Example 3 of the present invention;

[0052] Fig. 9 The diagram shows the water absorption effect of the electrostatic oil-cleaning hydrogels of Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0054] Example 1

[0055] The present embodiment provides an electrostatic oil-cleaning hydrogel, comprising the following raw materials in parts by weight: 1 part of sodium lignin sulfonate, 6 parts of chitosan, 65 parts of acrylic acid, 160 parts of 35wt% potassium hydroxide aqueous solution, 2 parts of potassium persulfate, 0.2 parts of N,N'-methylenebisacrylamide and 120 parts of deionized water.

[0056] The preparation method of the electrostatic oil-cleaning hydrogel comprises the following steps:

[0057] S1, weighing various raw materials according to the designed ratio, adding acrylic acid into a 35wt% potassium hydroxide aqueous solution, and conducting a neutralization reaction at room temperature for 1 minute to obtain an acrylate solution;

[0058] S2, adding sodium lignin sulfonate into deionized water, and after it is completely dissolved, adding chitosan, potassium persulfate and N,N'-methylenebisacrylamide, and mixing evenly to obtain a mixed solution;

[0059] S3, the acrylate solution and the mixed solution are mixed, and a cross-linking reaction is carried out at 80°C. After keeping the temperature for 2.5 hours, the brown hydrogel after the cross-linking reaction is washed with anhydrous ethanol until the washing liquid is colorless, and then placed in a constant temperature vacuum drying oven at 65°C and 750Pa, and vacuum dried for 3.5 hours to obtain the electrostatic oil-free hydrogel.

[0060] Example 2

[0061] The present embodiment provides an electrostatic oil-cleaning hydrogel, comprising the following raw materials in parts by weight: 2 parts of sodium lignin sulfonate, 8 parts of chitosan, 85 parts of acrylic acid, 200 parts of 50wt% potassium hydroxide aqueous solution, 3 parts of potassium persulfate, 0.3 parts of N,N'-methylenebisacrylamide and 150 parts of deionized water.

[0062] The preparation method of the electrostatic oil-cleaning hydrogel comprises the following steps:

[0063] S1, weighing various raw materials according to the designed ratio, adding acrylic acid into a 50wt% potassium hydroxide aqueous solution, and conducting a neutralization reaction at room temperature for 1 minute to obtain an acrylate solution;

[0064] S2, adding sodium lignin sulfonate into deionized water, and after it is completely dissolved, adding chitosan, potassium persulfate and N,N'-methylenebisacrylamide, and mixing evenly to obtain a mixed solution;

[0065] S3, mixing the acrylate solution and the mixed solution, performing a cross-linking reaction at 90°C, keeping the temperature for 2 hours, washing the brown hydrogel after the cross-linking reaction with anhydrous ethanol until the washing liquid is colorless, and then placing it in a constant temperature vacuum drying oven at 70°C and 800Pa, vacuum drying for 3 hours, and obtaining an electrostatic oil-free hydrogel.

[0066] Example 3

[0067] The present embodiment provides an electrostatic oil-cleaning hydrogel, comprising the following raw materials in parts by weight: 5 parts of sodium lignin sulfonate, 5 parts of chitosan, 50 parts of acrylic acid, 130 parts of 23wt% potassium hydroxide aqueous solution, 1 part of potassium persulfate, 0.1 parts of N,N'-methylenebisacrylamide and 100 parts of deionized water.

[0068] The preparation method of the electrostatic oil-cleaning hydrogel comprises the following steps:

[0069] S1, weighing various raw materials according to the designed ratio, adding acrylic acid into a 23wt% potassium hydroxide aqueous solution, and conducting a neutralization reaction at room temperature for 1 minute to obtain an acrylate solution;

[0070] S2, adding sodium lignin sulfonate into deionized water, and after it is completely dissolved, adding chitosan, potassium persulfate and N,N'-methylenebisacrylamide, and mixing evenly to obtain a mixed solution;

[0071] S3, mixing the acrylate solution and the mixed solution, performing a cross-linking reaction at 70°C, keeping the temperature for 3 hours, washing the brown hydrogel after the cross-linking reaction with anhydrous ethanol until the washing liquid is colorless, and then placing it in a constant temperature vacuum drying oven at 60°C and 700Pa, vacuum drying for 4 hours, and obtaining an electrostatic oil-free hydrogel.

[0072] The specific surface area and pore size analysis of the electrostatic clean oil hydrogels provided in Examples 1 to 3 were performed. The results are as follows: Figures 3 to 8 As shown. Figure 3 , 5 As can be seen from Figures 1 and 7, the N2 adsorption-desorption curves of the electrostatically clean oil hydrogel belong to the type IV isotherm (mesoporous adsorption), which is accompanied by a hysteresis loop after capillary condensation, and can be specifically a type IV a isotherm (when the pore width exceeds a certain critical width, hysteresis begins to occur). The adsorption characteristics of the mesopores are determined by the interaction between the adsorbent and the adsorbate, as well as the interaction between molecules in the condensed state. Figure 3 , 5 The curves of the knee-shaped parts in 7 and 8 are gradual bends without a clear inflection point, indicating that the coverage of the monolayer and the starting amount of multilayer adsorption are superimposed, rather than multilayer adsorption occurring only after the monolayer adsorption is completely completed; subsequently, condensation occurs in the pores (when the gas pressure P is less than the saturation pressure P0 of its liquid, it condenses into a liquid-like phase in the pores). In addition, the typical IV type isotherm is characterized by the formation of a final adsorption saturation platform, the length of which can be long or short, and Figure 3 , 5 No obvious platform appeared in and 7, indicating that the adsorption had not reached saturation.

[0073] from Figure 4 , 6As can be seen from Figures 1 and 8, the pores of the electrostatically cleaned oil hydrogels are all mesoporous structures with a width ranging from 2nm to 50nm; the electrostatically cleaned oil hydrogel of Example 2 has the largest pore structure, which is the reason for its obvious adsorption-desorption hysteresis loop (compared with the electrostatically cleaned oil hydrogels of Examples 1 and 3); the electrostatically cleaned oil hydrogel of Example 3 has a minimum pore size of 8.055nm and a maximum specific surface area of ​​40.808m 2 / g, the maximum pore volume is 0.11192cm 3 / g, it can be judged from a microscopic perspective that it has the best adsorption performance, which is consistent with the results of the subsequent water absorption test.

[0074] Take 0.4cm 3 The electrostatic clean oil hydrogels provided in Examples 1 to 3 were subjected to water absorption tests. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the electrostatic oil-cleaning hydrogel of Example 3 has the best water absorption performance. It can be understood that the addition of sodium lignin sulfonate changes the surface structure of the gel, making its surface rough and porous, increasing the contact area with water molecules, and showing a higher water absorption rate within 30 minutes of water absorption. However, after 30 minutes of water absorption, its volume expansion rate is similar to that of the electrostatic oil-cleaning hydrogels of Examples 1 to 2, and due to the roughness and porosity of the gel surface and excessive water absorption, the gel expands and breaks at 60 minutes of water absorption (it should be noted that the electrostatic oil-cleaning hydrogel can maintain structural stability in pure water within 60 minutes, and it will hardly break due to excessive water absorption in transformer oil with a low water content); the volume expansion rate of the electrostatic oil-cleaning hydrogel of Example 3 is the largest, and the volume expands to 23.0 cm at 65 minutes of water absorption. 3 The expansion rate is 57.5 times, and it still shows strong water absorption at this time; the water absorption rate of the electrostatic clean oil hydrogel in Example 1 is uniform and stable, and it shows a relatively uniform volume expansion rate within 65 minutes of water absorption.

[0075] Comparative Example 1

[0076] This comparative example provides a hydrogel, and its raw material components and proportions are similar to those of Example 3, except that the raw materials do not contain sodium lignin sulfonate.

[0077] The method for preparing the hydrogel comprises the following steps:

[0078] S1 is the same as in Example 3 and will not be described in detail;

[0079] S2, adding chitosan, potassium persulfate and N,N'-methylenebisacrylamide into deionized water and mixing them evenly to obtain a mixed solution;

[0080] S3, mixing the acrylate solution and the mixed solution, performing a cross-linking reaction at 70°C, keeping the temperature for 3 hours, washing the brown hydrogel after the cross-linking reaction with anhydrous ethanol until the washing solution is colorless, and then placing it in a constant temperature vacuum drying oven at 60°C and 700Pa, vacuum drying for 4 hours to obtain the hydrogel.

[0081] Electron microscope scanning was performed on the electrostatic clean oil hydrogels provided in Examples 1 to 3 and the hydrogel provided in Comparative Example 1. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the hydrogel without the addition of sodium lignin sulfonate is smooth. After the addition of sodium lignin sulfonate, wrinkles of varying degrees appear on the surface of the hydrogel. When the addition amount of sodium lignin sulfonate is 5 parts (Example 3), the surface roughness is the greatest.

[0082] The electrostatic clean oil hydrogels provided in Examples 1 to 3 and the hydrogel provided in Comparative Example 1 were tested for mechanical properties. The test results Figure 2 As shown. Figure 2 It can be seen that the tensile stress of the electrostatic clean oil hydrogel is 20MPa~30MPa, and the elongation at break is 35%~50%. After adding sodium lignin sulfonate, the tensile stress of the hydrogel is slightly increased.

[0083] Comparative Example 2

[0084] This comparative example provides a hydrogel, whose raw material components and proportions are similar to those of Example 3, except that chitosan is replaced by sodium alginate of the same mass.

[0085] The method for preparing the hydrogel comprises the following steps:

[0086] S1 is the same as in Example 3 and will not be described in detail.

[0087] S2, adding sodium lignin sulfonate into deionized water, and after it is completely dissolved, adding sodium alginate, potassium persulfate and N,N'-methylenebisacrylamide, and mixing them evenly to obtain a mixed solution;

[0088] S3, mixing the acrylate solution and the mixed solution, performing a cross-linking reaction at 70°C, keeping the temperature for 3 hours, washing the brown hydrogel after the cross-linking reaction with anhydrous ethanol until the washing solution is colorless, and then placing it in a constant temperature vacuum drying oven at 60°C and 700Pa, vacuum drying for 4 hours to obtain the hydrogel.

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a hydrogel, comprising the following steps:

[0091] S1, weighing each raw material according to the designed ratio (the raw material components and ratio are similar to those in Example 3, except that the 23wt% potassium hydroxide aqueous solution is replaced with deionized water of the same mass), adding sodium lignin sulfonate to 230 parts of deionized water, and after it is completely dissolved, adding chitosan, potassium persulfate and N,N'-methylenebisacrylamide, and mixing evenly to obtain a mixed solution;

[0092] S2, adding acrylic acid to the mixed solution, carrying out a cross-linking reaction at 70°C, and after keeping warm for 3 hours, it was found that no hydrogel could be obtained.

[0093] Comparative Example 4

[0094] This comparative example provides a method for preparing a hydrogel, comprising the following steps:

[0095] S1, weighing various raw materials according to the designed ratio (the raw material components and ratios are similar to those in Example 3, except that the 23wt% potassium hydroxide aqueous solution is replaced by an equal mass of 23wt% sodium bicarbonate aqueous solution), adding acrylic acid to the 23wt% sodium bicarbonate aqueous solution, and conducting a neutralization reaction at room temperature for 1 minute to obtain an acrylate solution;

[0096] S2 is the same as in Example 3 and will not be described in detail;

[0097] S3, adding the acrylate solution to the mixed solution, performing a cross-linking reaction at 70°C, and after keeping the temperature for 3 hours, it was found that no hydrogel could be obtained.

[0098] Application Example 1

[0099] This application example provides a method for using an electrostatic oil-cleaning hydrogel, comprising the following steps:

[0100] The electrostatic oil-cleaning hydrogel of Example 1 was placed at the oil inlet of the electrostatic oil-cleaning reactor, mixed with the circulating oil product to be purified (waste transformer oil, water content of 32.0 mg / L), and purified using a DC voltage. The volume ratio of the electrostatic oil-cleaning hydrogel to the oil product to be purified was 8.5 cm 3 :10L, the temperature of the electrostatic oil purification reactor (i.e., purification temperature) is 35°C, the DC voltage is 16kV, the circulation flow rate of the oil to be purified is 0.1m / s, and the purification time is 30min (1 cycle).

[0101] According to the test, the water content of the oil to be purified is 23.8 mg / L after purification.

[0102] Application Example 2

[0103] This application example provides a method for using an electrostatic oil-cleaning hydrogel, comprising the following steps:

[0104] The electrostatic oil-cleaning hydrogel of Example 2 was placed between the positive and negative electrode plates of the electrostatic oil-cleaning reactor, mixed with the circulating oil product to be purified (waste transformer oil, water content of 32.0 mg / L), and purified using a DC voltage. The volume ratio of the electrostatic oil-cleaning hydrogel to the oil product to be purified was 7.5 cm 3 :10L, the temperature of the electrostatic oil purification reactor (i.e., purification temperature) is 55°C, the DC voltage is 12kV, the circulation flow rate of the oil to be purified is 0.3m / s, and the purification time is 30min (1 cycle).

[0105] According to the test, the water content of the oil to be purified is 23.2 mg / L after purification.

[0106] Application Example 3

[0107] This application example provides a method for using an electrostatic oil-cleaning hydrogel, comprising the following steps:

[0108] The electrostatic oil-cleaning hydrogel of Example 3 was attached to the positive electrode plate of the electrostatic oil-cleaning reactor, mixed with the circulating oil product to be purified (waste transformer oil, water content of 32.0 mg / L), and purified using a DC voltage. The volume ratio of the electrostatic oil-cleaning hydrogel to the oil product to be purified was 8 cm 3 :10L, the temperature of the electrostatic oil purification reactor (i.e., purification temperature) is 45°C, the DC voltage is 14kV, the circulation flow rate of the oil to be purified is 0.2m / s, and the purification time is 30min (1 cycle).

[0109] According to the test, the water content of the oil to be purified is 22.9 mg / L after purification.

[0110] Application Example 4

[0111] This application example provides a method for using an electrostatic oil-cleaning hydrogel, which is similar to application example 3, except that the purification time is extended to 300 min (10 cycles). Other conditions are the same as those in application example 3 and will not be described in detail.

[0112] After testing, the water content of the purified oil was 21.0 mg / L. In addition, the performance of the electrostatic oil-cleaning hydrogel did not decrease significantly.

[0113] Application Comparative Example 1

[0114] This comparative application example provides a method for using a hydrogel, which is similar to Application Example 3, except that the electrostatic oil-free hydrogel in Example 3 is replaced by the hydrogel in Comparative Example 1. Other conditions are the same as those in Application Example 3 and will not be described in detail.

[0115] According to the test, the water content of the oil to be purified is 26.0 mg / L after purification.

[0116] Application Comparative Example 2

[0117] This comparative application example provides a method for using a hydrogel, which is similar to Application Example 3, except that the electrostatic oil-free hydrogel in Example 3 is replaced by the hydrogel in Comparative Example 2. Other conditions are the same as those in Application Example 3 and will not be described in detail.

[0118] According to the test, the water content of the oil to be purified is 26.4 mg / L after purification.

[0119] Application Comparative Example 3

[0120] This comparative example provides a method for purifying waste transformer oil, which is similar to Example 3, except that the electrostatic oil-cleaning hydrogel of Example 3 is omitted. The method specifically comprises the following steps:

[0121] The circulating oil product to be purified (waste transformer oil, water content of 32.0 mg / L) was purified by direct current voltage (no electrostatic oil purification hydrogel was placed in the electrostatic oil purification reactor). The temperature of the electrostatic oil purification reactor (i.e., purification temperature) was 45°C, the direct current voltage was 14kV, the circulation velocity of the oil product to be purified was 0.2m / s, and the purification time was 30min.

[0122] According to the test, the water content of the oil to be purified is 27.4 mg / L after purification.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrostatic oil-cleaning hydrogel, characterized in that: The invention comprises the following raw materials in parts by weight: 1 to 6 parts of lignin sulfonate, 5 to 8 parts of chitosan, 50 to 85 parts of acrylic acid, 130 to 200 parts of strong alkali solution, 1 to 3 parts of initiator, 0.1 to 0.3 parts of cross-linking agent and 100 to 150 parts of water.

2. The electrostatic oil-cleaning hydrogel according to claim 1, characterized in that: The lignin sulfonate includes sodium lignin sulfonate; The strong alkaline solution comprises 20wt% to 50wt% potassium hydroxide aqueous solution; The initiator includes potassium persulfate; The cross-linking agent includes N,N'-methylenebisacrylamide.

3. The electrostatic oil-cleaning hydrogel according to claim 1, characterized in that: The electrostatic clean oil hydrogel is a mesoporous structure; The specific surface area of ​​the electrostatic clean oil hydrogel is 36 m 2 / g~42m 2 / g, pore volume is 0.01m 3 / g~0.113m 3 / g.

4. The electrostatic oil-cleaning hydrogel according to claim 1, characterized in that: The electrostatic clean oil hydrogel is prepared from the raw materials through a sol-gel method.

5. The method for preparing the electrostatic clean oil hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, weighing various raw materials according to the designed ratio, adding acrylic acid into a strong alkaline solution to carry out a neutralization reaction to obtain an acrylic acid salt solution; S2, adding lignin sulfonate, chitosan, an initiator and a cross-linking agent into water to obtain a mixed solution; S3, mixing the acrylate solution and the mixed solution, and performing a cross-linking reaction at 70° C. to 90° C. to obtain an electrostatic clean oil hydrogel.

6. The method for preparing the electrostatic clean oil hydrogel according to claim 5, characterized in that: In S1, the neutralization reaction temperature is 5°C to 40°C, and the reaction time is 0.5min to 1.5min; In S3, the cross-linking reaction time is 2h to 3h.

7. Use of the electrostatic oil-cleaning hydrogel according to any one of claims 1 to 4 in dehydration of industrial oil products.

8. The method for using the electrostatic oil-cleaning hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: The electrostatic oil-cleaning hydrogel is mixed with the circulating oil product to be purified for purification.

9. The method for using the electrostatic oil-cleaning hydrogel according to claim 8, characterized in that: The volume ratio of the electrostatic oil-cleaning hydrogel to the oil to be purified is (7.5-8.5) cm 3 :10L; The electrostatic oil purification hydrogel is placed on at least one of the positive electrode plate, the negative electrode plate, between the positive and negative electrode plates or at the oil inlet of the electrostatic oil purification reactor.

10. The method for using the electrostatic oil-cleaning hydrogel according to claim 8, characterized in that: The purification temperature is 35°C to 55°C; The purification adopts a DC voltage, and the DC voltage is 12kV to 16kV; The circulation velocity of the oil product to be purified is 0.1m / s to 0.3m / s; The purification time is 25min to 40min.

Citation Information

Patent Citations

  • Sodium lignosulfonate chitosan hydrogel, and preparation method thereof

    CN109897197A

  • Antistatic super absorbent resin as well as preparation method and application thereof

    CN111793226A

  • Video tape recorder

    JP1993056385A